2012
DOI: 10.4093/dmj.2012.36.2.136
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Recently Diagnosed Type 2 Diabetes Patients with Positive Anti-Glutamic Acid Decarboxylase Antibody

Abstract: BackgroundLatent autoimmune diabetes in adults (LADA) refers to a specific type of diabetes characterized by adult onset, presence of islet auto-antibodies, insulin independence at the time of diagnosis, and rapid decline in β-cell function. The prevalence of LADA among patients with type 2 diabetes varies from 2% to 20% according to the study population. Since most studies on the prevalence of LADA performed in Korea were conducted in patients who had been tested for anti-glutamic acid decarboxylase antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
1
19
0
3
Order By: Relevance
“…In other racial groups, such as African‐Americans and Hispanics, the prevalence of LADA is lower than in white people . Studies from Asian countries such as China, Japan and Korea report a relatively low prevalence of 4–6% for LADA .…”
Section: Introductionmentioning
confidence: 99%
“…In other racial groups, such as African‐Americans and Hispanics, the prevalence of LADA is lower than in white people . Studies from Asian countries such as China, Japan and Korea report a relatively low prevalence of 4–6% for LADA .…”
Section: Introductionmentioning
confidence: 99%
“…Factually, guidelines on LADA treatment do not exist and is controversial whether sulphonylurea, insulin, vitamin D or alternative therapies such as GAD65, can influence the beta-cell loss progression and metabolic control [59] . Since LADA patients are presented not only with gradually developing insulin deficiency, but also with insulin resistance, a unique treatment strategy should be designed, in order to treat hyperglycaemia and to preserve b-cell function [60] .…”
Section: Characteristicsmentioning
confidence: 99%
“…In the present study, the rate of anti‐GAD Ab in the patients with T2DM was found to be 8.3%. The reported prevalence rates of anti‐GAD Ab in Korean patients with T2DM ranges from 1.7% to 12.6% . It has also been reported that patients with low titres (<10 U) of anti‐GAD Ab exhibit significantly higher C‐peptide levels than those with high titres (≥10 U); there were no insulin‐users among participants with low titres of anti‐GAD Ab .…”
Section: Discussionmentioning
confidence: 99%
“…The reported prevalence rates of anti‐GAD Ab in Korean patients with T2DM ranges from 1.7% to 12.6% . It has also been reported that patients with low titres (<10 U) of anti‐GAD Ab exhibit significantly higher C‐peptide levels than those with high titres (≥10 U); there were no insulin‐users among participants with low titres of anti‐GAD Ab . Another follow‐up study of Korean patients reported that only 3 of 39 patients who were initially classified as having late autoimmune diabetes in adults (LADA) became insulin‐dependent after 36 months; these 3 patients were all positive for multiple autoantibodies (GAD, islet antigen 2, and zinc transporter 8 antibody).…”
Section: Discussionmentioning
confidence: 99%